The relationship between occurrence of crime and economic growth in European Union (Panel Var Approach) - Nayebyazdi, Arash (International Journal of Contemporary Economics and Administrative Sciences, 2017)
This study is to evaluate the relationship between crime and economic growth in 27 countries of EU in the time period of 2004 – 2014. Using GMM estimators of Panel Var model and Granger causality test, shock effects of crime occurrence on economic growth in these countries are analyzed. For this purpose control variables of government spending on education in percentage, investment per capita and population have also been used. Based on the gain results economic growth in relationship to crime occurrence has a significant reaction but in a negative way, though after a shock on economic growth, crime would have a positive effect. The reason for this can be found in Kuznets curve. Due to the fact that in the early stages of economic growth, there is more income inequality and income inequality leads to crime occurrence, over time the impact of crime on economic growth has decreased and has reached from 9% in the first period to 6.5% in the second. Therefore, the attendance of new countries of East Europe in the EU, by considering the average of crime in them, can be a threat to economic growth of other members of this union.